Deletion of Herpud1 Enhances Heme Oxygenase-1 Expression in a Mouse Model of Parkinson’s Disease - Thuong Manh Le (Parkinson's Disease, 2016)
Herp is an endoplasmic reticulum- (ER-) resident membrane protein that plays a role in ER-associated degradation. We studied the expression of Herp and its effect on neurodegeneration in a mouse model of Parkinson’s disease (PD), in which both the oxidative stress and the ER stress are evoked. Eight hours after administering a PD-related neurotoxin, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), to mice, the expression of Herp increased at both the mRNA and the protein levels. Experiments using Herpud1+/+ and Herpud1−/− mice revealed that the status of acute degeneration of nigrostriatal neurons and reactive astrogliosis was comparable between two genotypes after MPTP injection. However, the expression of a potent antioxidant, heme oxygenase-1 (HO-1), was detected to a higher degree in the astrocytes of Herpud1−/− mice than in the astrocytes of Herpud1+/+ mice 24 h after MPTP administration. Further experiments using cultured astrocytes revealed that the stress response against MPP+, an active form of MPTP, and hydrogen peroxide, both of which cause oxidative stress, was comparable between the two genotypes. These results suggest that deletion of Herpud1 may cause a slightly higher level of initial damage in the nigrastrial neurons after MPTP administration but is compensated for by higher induction of antioxidants such as HO-1 in astrocytes.